Carbon-silicon composite material and preparation method and application thereof

By burning the carbon-silicon composite material prepared by pyrogen rubber, coal tar and silica aerogel, the problem that carbon black in sealed products is difficult to improve high temperature and wear resistance, and the high temperature and wear resistance of sealed products is achieved Improved performance and extended service life.

CN119264518APending Publication Date: 2025-01-07GUANGDONG POWER GRID CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411380650.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing carbon black is difficult to meet the needs of improving high temperature and wear resistance in sealed products, and its density is high, resulting in poor thermal conductivity, affecting the service life of rubber sealed products.

Method used

Using carbon-silicon composite materials, by mixing and burning the polybutyl rubber, coal tar and silica aerogel, a carbon-silicon composite material with ultra-low density and tubular hollow structure is prepared, combining its high specific surface area and low density characteristics. Improve the high temperature and wear resistance of sealed products.

Benefits of technology

It achieves the improvement of high temperature resistance and wear resistance of sealed products, while reducing rolling resistance and heat generation performance, and extending the service life of rubber products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264518A_ABST
    Figure CN119264518A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-silicon composite material as well as a preparation method and application thereof, and relates to the technical field of carbon black preparation. Comprising the following steps: (1) mixing ethylene-butadiene rubber, silicon dioxide aerogel and coal tar to obtain premixed feed liquid; (2) conveying the premixed feed liquid to a reaction chamber for combustion reaction to obtain mixed flue gas; (3) introducing the mixed flue gas into heat exchange equipment for cooling; (4) cooling the mixed flue gas, feeding the cooled mixed flue gas into a filter bag filtering system for flue gas separation, collecting carbon-silicon composite material particles by a filter bag, feeding the carbon-silicon composite material particles into a nano crusher through a conveying system for crushing, and preparing the blocky carbon-silicon composite material into powder; and (5) preparing the powdery carbon-silicon composite material into particles, and drying to obtain the carbon-silicon composite material. The carbon-silicon composite material disclosed by the invention has the characteristics of stable chemical performance and small density, and when the carbon-silicon composite material is applied to a rubber sealing product, the wear resistance and the aging resistance of the sealing product are favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon black preparation, and in particular to a carbon-silicon composite material and a preparation method and application thereof. Background Art

[0002] As an important rubber reinforcing material, carbon black has a complex structure and high surface chemical activity. It can be firmly combined with the rubber surface, effectively improving the physical properties and aging resistance of rubber, thereby extending the service life of rubber products. Therefore, it is widely used in tires, sealing products, conveyor belts, hoses and other fields.

[0003] Carbon black is widely used in rubber sealing products. Carbon black provides rubber reinforcement and improves hardness, and also improves aging resistance. However, with the changes in the use environment of sealing products, higher requirements are placed on reinforcing materials, which require better high temperature resistance and wear resistance. Aerogel and carbon black are made into composite materials. The ultra-low density tubular structure of aerogel effectively improves the high temperature resistance of sealing products. The carbon-silicon composite effectively reduces the rolling resistance of the mixed rubber, while improving wear resistance and reducing heat generation. Therefore, it is necessary to develop new reinforcing materials to improve sealing products. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a carbon-silicon composite material and a preparation method and application thereof. The carbon-silicon composite material of the present invention has the characteristics of stable chemical properties and low density. When applied to rubber sealing products, it is beneficial to improve the wear resistance and aging resistance of the sealing products.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect, the present invention provides a method for preparing a carbon-silicon composite material, comprising the following steps:

[0007] (1) mixing 5-10 parts by weight of ethylene-butadiene rubber, 5-10 parts by weight of silica aerogel and 100-140 parts by weight of coal tar to obtain a premix liquid;

[0008] (2) The premix liquid is transported to the reaction chamber for combustion reaction, natural gas is used as fuel, the reaction temperature is controlled at 1700-1900°C, the reaction time is controlled at 5-9ms, tap water is used to atomize the flame to extinguish the combustion reaction, and a mixed flue gas is obtained;

[0009] (3) passing the generated mixed flue gas into a heat exchange device for cooling, and the temperature after cooling is controlled below 280°C;

[0010] (4) The mixed flue gas is cooled and enters the filter bag filtration system for flue gas separation. The filter bag collects carbon-silicon composite material particles, and the vibration system is started to remove the carbon-silicon composite material from the filter bag. The carbon-silicon composite material is crushed by the nano-crusher through the conveying system, and the blocky carbon-silicon composite material is made into powder;

[0011] (5) The powdered carbon-silicon composite material enters a granulator through a pipeline, and is formed into granules under tap water atomization and a high-speed rotating granulation system. After drying, the carbon-silicon composite material is obtained.

[0012] Silica aerogel is a solid material with excellent thermal insulation performance. It has a special microstructure with high specific surface area, nano-scale pores, low density, etc. Based on these structures, it exhibits excellent thermal performance. Its thermal conductivity is ~0.012mw / mk and density is ~0.16mg / cm 3 Specific surface area is 400-1000m 2 / g, porosity is 90-99.8%, it has stable chemical properties, 99% of its internal volume is composed of gas, it is the solid with the smallest density known so far, it can effectively insulate and at the same time improve the aging resistance of the product.

[0013] The present invention mixes aerogel with ethylene-butadiene rubber and coal tar to obtain a premixed liquid, which enters a reaction chamber for combustion to prepare a carbon-silicon composite material of carbon black and aerogel. The carbon-silicon composite material of the present invention has the characteristics of stable chemical properties and low density. When it is applied to rubber sealing products, the ultra-low-density tubular hollow structure of the aerogel is conducive to reducing the thermal conductivity of the material itself, thereby improving the high-temperature resistance of the rubber sealing products. In addition, the combination of carbon and silicon effectively reduces the rolling resistance of the mixed rubber, improves elasticity, improves sealing performance, and is also conducive to improving the wear resistance of the sealing products.

[0014] Preferably, in step (1), the weight average molecular weight of the ethylene-butadiene rubber is 250,000-450,000.

[0015] Preferably, in step (1), the particle size of the silica aerogel is 15-20 nm.

[0016] In the present invention, if the particle size of the silica aerogel is too large, the specific surface area becomes smaller, the chemical bonding surface is reduced, and the performance of the carbon-silicon composite material is reduced; if the particle size of the silica aerogel is too small, it is easy to cause dispersion difficulties, so that the product quality of the product is affected. Therefore, the present invention is beneficial to improve the wear resistance and aging resistance of the rubber sealing product by controlling the particle size of the silica aerogel within the above range.

[0017] Preferably, in step (1), the specific mixing steps of the premix liquid are as follows:

[0018] S1: First, the ethylene-butadiene rubber is melted, and the melting temperature is controlled at 65-70°C; after melting for 1-2 minutes, the ethylene-butadiene rubber is cut into pieces, and the pieces are left for 6-8 hours before being cooled to room temperature;

[0019] S2: Put coal tar into a stirring tank, control the temperature at 160-170°C, put ethylene-butadiene rubber into the stirring tank, stir at a speed of 70-90 rpm, and stir for 15-20 min;

[0020] S3: After the ethylene-butadiene rubber and coal tar are completely dissolved, add the silica aerogel and stir for 10-12 minutes. After mixing evenly, a premix liquid is obtained.

[0021] Preferably, in step (2), the premix liquid and air are sprayed into the reaction chamber together through a nozzle, the flow rate of the premix liquid is 450-550 m / s, the volume ratio of the premix liquid to air is 1:(15-25), natural gas is used as fuel to produce flames, and tap water is used for atomization to end the chemical reaction.

[0022] In the present invention, the role of introducing air is to atomize the raw material oil (premix liquid) better. The ratio of air to premix liquid is called the air-oil ratio. If it is too large, the production efficiency is too low. If it is too small, the atomization of the premix liquid is insufficient, and the particle size distribution of the fired carbon black is too wide, which is easy to cause the physical properties of the product to decrease. Therefore, the present invention is beneficial to improving the quality of rubber products by controlling the volume ratio of the premix liquid and air within the above range.

[0023] Moreover, the flow rate of the premix liquid will directly affect the change in the performance of the carbon-silicon composite material. If the flow rate is too low, the production yield of the carbon-silicon composite material will be directly reduced (the yield will be reduced) and the degree of matching with the subsequent procedures. If the flow rate is too high, the relative atomization degree will be reduced, the atomization degree will be uneven, and coking will occur during the combustion process, which will widen the particle size distribution of the carbon-silicon composite material and reduce the physical properties. Therefore, the present invention is conducive to improving the performance of rubber products by controlling the flow rate of the premix liquid within the above range.

[0024] Preferably, in step (4), the rotation speed of the nano-crusher is 2800-3000 rpm, and the crushing time is 5-8 s.

[0025] Preferably, in step (5), during granulation, the mass ratio of the powdered carbon-silicon composite material to water is 1:(0.65-0.75).

[0026] Preferably, in step (5), the drying temperature is 230-255° C., and the moisture content of the powder after drying is controlled to be ≤0.3-0.6%.

[0027] In a second aspect, the present invention further provides a carbon-silicon composite material prepared by the above method, with a particle size of 50-80 nm.

[0028] In a third aspect, the present invention further provides an application of a carbon-silicon composite material in a rubber sealing product, wherein the rubber sealing product comprises the following components in parts by weight:

[0029] 100 parts of ethylene-butadiene rubber; 45-55 parts of carbon-silicon composite material; 1-2 parts of coupling agent; 1-4 parts of antioxidant; 3-5 parts of zinc oxide; 1.5-2 parts of stearic acid; 1-2 parts of protective wax; 1.5-2.5 parts of accelerator; 0.2-0.4 parts of vulcanizing agent.

[0030] Preferably, the coupling agent is coupling agent SI-69.

[0031] Preferably, the antioxidant includes at least one of antioxidant RD and antioxidant NBC.

[0032] Preferably, the accelerator includes at least one of thiazole, xanthocyanamide, thiuram and DTDM accelerators.

[0033] More preferably, the thiazoles are accelerator DM, the xanthocyanamides are accelerator NS and accelerator CZ, and the thiurams are accelerator TMTD.

[0034] Preferably, the vulcanizing agent includes sulfur and vulcanizing agent DCP.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The carbon-silicon composite material of the present invention has the characteristics of stable chemical properties and low density. When it is applied to rubber sealing products, the ultra-low-density tubular hollow structure of the aerogel is conducive to reducing the thermal conductivity of the material itself, thereby improving the high-temperature resistance of the rubber sealing products. In addition, the combination of carbon and silicon effectively reduces the rolling resistance of the mixed rubber, improves elasticity, improves sealing performance, and also improves the wear resistance of the sealing products. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is an electron microscope scanning image of the carbon-silicon composite material prepared in Example 1 of the present invention.

[0038] Figure 2 This is an electron microscope scan of national standard N330 carbon black. DETAILED DESCRIPTION

[0039] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the protection scope and implementation methods of the present invention are not limited thereto.

[0040] Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0041] 1. Raw materials:

[0042] Ethylene-butadiene rubber, K-9330M, Shanghai Sinopec Mitsui Elastomer Co., Ltd., weight average molecular weight is 380,000;

[0043] Silica aerogel, powder, Nanomate New Material Technology Co., Ltd.;

[0044] Coal tar, viscous liquid, Hebei Xuyang Coking Co., Ltd.;

[0045] National standard N330 carbon black, Cabot (China) Investment Co., Ltd.

[0046] 2. Main equipment and instruments:

[0047] XK-160 mixing mill, Shanghai Rubber Machinery Factory; XLB flat vulcanizer, Qingdao Third Rubber Machinery Factory; TIO tensile testing machine, product of Alpha Technology Co., Ltd., USA; rubber hardness tester, Shanghai Machinery Factory; Akron abrasion testing machine, product of Shanghai Chemical Machinery Factory, LM multi-channel air tightness tester; GT-RH-2000 compression heat tester, China Taiwan High Speed ​​Rail Technology Co., Ltd.

[0048] The following examples and comparative examples all use the above-mentioned raw materials and instruments.

[0049] Example 1

[0050] This embodiment discloses a method for preparing a carbon-silicon composite material, comprising the following steps:

[0051] (1) 5 parts by weight of ethylene-butadiene rubber, 5 parts by weight of silica aerogel and 100 parts by weight of coal tar are mixed to obtain a premix liquid; the particle size of the silica aerogel is 15 nm;

[0052] The specific mixing steps of the premix liquid are as follows:

[0053] S1: First, the ethylene-butadiene rubber is refined on an open mill, and the temperature of the roller of the open mill is controlled at 70°C; after refining for 2 minutes, the ethylene-butadiene rubber is cut into sheets with the size of 300mm in width and 2mm in thickness, and the sheets are left for 8 hours to cool to room temperature;

[0054] S2: Cut into small pieces of 10mm*10mm with a cutting machine; at the same time, put coal tar into a mixing tank, control the temperature at 160℃, cut ethylene-butadiene rubber into small pieces of 10mm*10mm and put them into the mixing tank, the stirring speed is 70 rpm, and the total stirring time is 15min;

[0055] S3: After the ethylene-butadiene rubber and coal tar are completely dissolved, add the silica aerogel and stir for a total of 10 minutes. After mixing evenly, a premix liquid is obtained. The premix liquid is then transported to a storage tank for storage at a temperature of 120°C. At the same time, low-speed stirring is performed at a stirring speed of 15 rpm.

[0056] (2) The premix liquid is transported to the furnace reaction chamber by a high-pressure pump for combustion reaction, and air is sprayed into the reaction chamber through a nozzle. Natural gas is used as fuel. The reaction temperature is 1700°C, the reaction time is 5ms, and the flame is extinguished by tap water atomization to terminate the combustion reaction and obtain mixed flue gas. The flow rate of the premix liquid is 450m / s, and the volume ratio of the premix liquid to air is 1:15.

[0057] (3) The generated mixed flue gas is passed through the heat exchange equipment for cooling. The heat exchanger sends part of the excess heat to the energy center for power generation and the other part is used for the heating system. After cooling, the temperature is controlled below 280°C to ensure that the filter bag is not damaged by high temperature.

[0058] (4) After cooling, the mixed flue gas enters the filter bag filtration system for flue gas separation. The filter bag collects the carbon-silicon composite material particles, and the vibration system is started to remove the carbon-silicon composite material from the filter bag. The carbon-silicon composite material enters the nano-crusher through a closed transmission system for crushing, and the blocky carbon-silicon composite material is made into powder. The speed of the nano-crusher is 2900 rpm, and the crushing time is 5 s.

[0059] (5) The powdered carbon-silicon composite material enters a granulator through a pipeline, is atomized by tap water and is granulated by a high-speed rotating granulation system, and then enters a dryer for drying to remove moisture generated during the granulation process. The temperature of the dryer is 230° C., and finally enters a storage and packaging system. During granulation, the mass ratio of the powdered carbon-silicon composite material to water is 1:0.65.

[0060] This embodiment also discloses a method for preparing a vulcanized test piece of a rubber sealing product, comprising the following steps:

[0061] (1) The temperature of the open mill roll was adjusted to 75°C, 100 g of ethylene-butadiene rubber was added to the roll, the amount of rubber accumulation was adjusted, and 50 g of carbon-silicon composite material and 1.5 g of coupling agent SI-69 were added successively.

[0062] (2) When the carbon-silicon composite material is completely powdered, 4g zinc oxide, 1.5g stearic acid, 2.0g antioxidant NBC, 1.3g antioxidant RD and 1g protective wax are added. After all the powder is eaten, the roller distance is adjusted to 3mm, three thin passes are made, and three triangle packages are made. The roller distance is adjusted to 6mm, 0.13g sulfur and DCP, 0.15g CZ accelerator, 1.1g TMTD accelerator, and 0.75g DTDM accelerator are added. After eating the powder, three thin passes are made, and three triangle packages are made. Finally, the roller distance is adjusted and the film is removed. It is parked for 8h and a vulcanized test piece is carried out. The mixed rubber is vulcanized on a vulcanizer. The vulcanization temperature is 155°C and the vulcanization time is 25min. After cutting, the test film has a thickness of 2.0mm and a size of 2*150*120mm.

[0063] Example 2

[0064] This embodiment discloses a method for preparing a carbon-silicon composite material, comprising the following steps:

[0065] (1) 10 parts by weight of ethylene-butadiene rubber, 10 parts by weight of silica aerogel and 140 parts by weight of coal tar are mixed to obtain a premix liquid; the particle size of the silica aerogel is 20 nm;

[0066] The specific mixing steps of the premix liquid are as follows:

[0067] S1: First, the ethylene-butadiene rubber is refined on an open mill, and the temperature of the roller of the open mill is controlled at 70°C; after refining for 2 minutes, the ethylene-butadiene rubber is cut into sheets with the size of 300mm in width and 2mm in thickness, and the sheets are left for 8 hours to cool to room temperature;

[0068] S2: Cut into small pieces of 10mm*10mm with a cutting machine; at the same time, put coal tar into a mixing tank, control the temperature at 170℃, cut ethylene-butadiene rubber into small pieces of 10mm*10mm and put them into the mixing tank, the stirring speed is 90 rpm, and the total stirring time is 20min;

[0069] S3: After the ethylene-butadiene rubber and coal tar are completely dissolved, add the silica aerogel and stir for a total of 12 minutes. After mixing evenly, a premix liquid is obtained. The premix liquid is then transported to a storage tank for storage at a temperature of 135°C. At the same time, low-speed stirring is performed at a speed of 20 revolutions per minute.

[0070] (2) The premix liquid is transported to the furnace reaction chamber by a high-pressure pump for combustion reaction, and air is sprayed into the reaction chamber through a nozzle. Natural gas is used as fuel. The reaction temperature is 1900°C, the reaction time is 9ms, and the flame is extinguished by tap water atomization to terminate the combustion reaction and obtain mixed flue gas. The flow rate of the premix liquid is 550m / s, and the volume ratio of the premix liquid to air is 1:25.

[0071] (3) The generated mixed flue gas is passed through the heat exchange equipment for cooling. The heat exchanger sends part of the excess heat to the energy center for power generation and the other part is used for the heating system. After cooling, the temperature is controlled below 280°C to ensure that the filter bag is not damaged by high temperature.

[0072] (4) After cooling, the mixed flue gas enters the filter bag filtration system for flue gas separation. The filter bag collects the carbon-silicon composite material particles, and the vibration system is started to remove the carbon-silicon composite material from the filter bag. The carbon-silicon composite material enters the nano-crusher through a closed transmission system for crushing, and the blocky carbon-silicon composite material is made into powder. The speed of the nano-crusher is 3000 rpm, and the crushing time is 8 s.

[0073] (5) The powdered carbon-silicon composite material enters the granulator through a pipeline, is atomized by tap water and is granulated by a high-speed rotating granulation system, and then enters a dryer for drying to remove moisture generated during the granulation process. The temperature of the dryer is 255° C., and finally enters a storage and packaging system. During granulation, the mass ratio of the powdered carbon-silicon composite material to water is 1:0.75.

[0074] This embodiment also discloses a method for preparing a vulcanized test piece of a rubber sealing product, comprising the following steps:

[0075] (1) The temperature of the open mill roll was adjusted to 75°C, 100 g of ethylene-butadiene rubber was added to the roll, the amount of rubber accumulation was adjusted, and 50 g of carbon-silicon composite material and 1.5 g of coupling agent SI-69 were added successively.

[0076] (2) When the carbon-silicon composite material is completely powdered, 4g zinc oxide, 1.5g stearic acid, 2.0g antioxidant NBC, 1.3g antioxidant RD and 1g protective wax are added. After all the powder is eaten, the roller distance is adjusted to 3mm, three thin passes are made, and three triangle packages are made. The roller distance is adjusted to 6mm, 0.13g sulfur and DCP, 0.15g CZ accelerator, 1.1g TMTD accelerator, and 0.75g DTDM accelerator are added. After eating the powder, three thin passes are made, and three triangle packages are made. Finally, the roller distance is adjusted and the film is removed. It is parked for 8h and a vulcanized test piece is carried out. The mixed rubber is vulcanized on a vulcanizer. The vulcanization temperature is 155°C and the vulcanization time is 25min. After cutting, the test film has a thickness of 2.0mm and a size of 2*150*120mm.

[0077] Example 3

[0078] A method for preparing a carbon-silicon composite material, which is different from that in Example 1 in that, in step (1), 5 parts by weight of ethylene-butadiene rubber, 7.5 parts by weight of silica aerogel and 120 parts by weight of coal tar are mixed to obtain a premix liquid, and the rest are the same as in Example 1.

[0079] Comparative Example 1

[0080] A method for preparing a carbon-silicon composite material, which is different from that of Example 1 in that, in step (1), 5 parts by weight of ethylene-butadiene rubber, 2 parts by weight of silica aerogel and 100 parts by weight of coal tar are mixed to obtain a premix liquid, and the rest are the same as those of Example 1.

[0081] Comparative Example 2

[0082] A method for preparing a carbon-silicon composite material, which is different from that of Example 1 in that, in step (1), 5 parts by weight of ethylene-butadiene rubber, 12 parts by weight of silica aerogel and 100 parts by weight of coal tar are mixed to obtain a premix liquid, and the rest are the same as those of Example 1.

[0083] Comparative Example 3

[0084] A method for preparing a vulcanized test piece of a rubber sealing product, using national standard N330 carbon black of equal mass to replace the carbon-silicon composite material, and the rest is the same as in Example 1.

[0085] Comparative Example 4

[0086] A method for preparing a carbon-silicon composite material, which is different from that in Example 1 in that, in step (1), 4.5 parts by weight of ethylene-butadiene rubber, 1.5 parts by weight of silica aerogel and 95 parts by weight of coal tar are mixed to obtain a premix liquid, and the rest are the same as in Example 1.

[0087] Comparative Example 5

[0088] A method for preparing a carbon-silicon composite material, which is different from that in Example 1 in that, in step (1), 10.5 parts by weight of ethylene-butadiene rubber, 5.5 parts by weight of silica aerogel and 145 parts by weight of coal tar are mixed to obtain a premix liquid, and the rest are the same as in Example 1.

[0089] Comparative Example 6

[0090] A method for preparing a carbon-silicon composite material, which differs from that of Example 1 in that, in step (1), an equal mass of ethylene-propylene rubber is used to replace ethylene-butyl rubber, and the rest is the same as that of Example 1.

[0091] Comparative Example 7

[0092] A method for preparing a carbon-silicon composite material, which is different from that of Example 1 in that, in step (2), the reaction temperature is 1600° C., and the rest is the same as that of Example 1.

[0093] Comparative Example 8

[0094] A method for preparing a carbon-silicon composite material, which is different from that of Example 1 in that, in step (2), the reaction temperature is 2000° C., and the rest is the same as that of Example 1.

[0095] Comparative Example 9

[0096] A method for preparing a carbon-silicon composite material, which is different from that of Example 1 in that, in step (2), the reaction time is 2 ms, and the rest is the same as that of Example 1.

[0097] Comparative Example 10

[0098] A method for preparing a carbon-silicon composite material, which is different from that of Example 1 in that, in step (2), the reaction time is 12 ms, and the rest is the same as that of Example 1.

[0099] Performance testing:

[0100] 1. The carbon-silicon composite materials prepared in Examples 1-3, Comparative Examples 1-2 and 4-10 and the national standard N330 carbon black described in Comparative Example 3 were tested for iodine absorption value, specific surface area, tinting strength, DBP, CDBP and 325 sieve residue performance. The test results are shown in Table 1.

[0101] Table 1

[0102]

[0103] According to Table 1, the iodine absorption value, specific surface area and tinting strength of the carbon-silicon composite material prepared in the embodiment are all greater than those in comparative example 1, indicating that the present invention obtains a carbon-silicon composite material of carbon black and aerogel by mixing silica aerogel with ethylene-butadiene rubber and coal tar to obtain a premixed liquid, which enters the reaction chamber for combustion together, and has the characteristics of low density and stable chemical properties.

[0104] according to Figure 1 and Figure 2 By comparison, Figure 1 The relative surface area Figure 2 Smaller (relatively larger particle size) structures are relatively lower.

[0105] 2. After the vulcanized test pieces prepared in Examples 1-3 and Comparative Examples 1-10 were vulcanized for 20 minutes, the Shore A hardness, 50% tensile stress at modulus, 100% tensile stress at modulus, 200% tensile stress at modulus, 300% tensile stress at modulus, tensile strength and elongation were tested according to GB / T 528-2009 standard.

[0106] 3. According to GB / T 7755-2003 standard, the vulcanized test pieces prepared in Examples 1-3 and Comparative Examples 1-10 were tested for air permeability, compression fatigue temperature rise and Akron abrasion.

[0107] The above test results are shown in Table 2 and Table 3.

[0108] Table 2

[0109]

[0110] Table 3

[0111]

[0112]

[0113] According to Table 3, the tensile strength and elongation of the vulcanized test piece of the rubber sealing product described in the embodiment are higher than those of the comparative example, indicating that the vulcanized test piece of the rubber sealing product prepared by the present invention has excellent mechanical properties. In addition, the air permeability coefficient, compression fatigue temperature rise and Akron wear loss of the vulcanized test piece of the rubber sealing product described in the embodiment are lower than those of the comparative example, indicating that the present invention applies the carbon silicon composite material to the vulcanized test piece of the rubber sealing product, so that the vulcanized test piece also has excellent wear resistance and aging resistance.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a carbon-silicon composite material, characterized in that: The following steps are involved: (1) mixing 5-10 parts by weight of ethylene-butadiene rubber, 5-10 parts by weight of silica aerogel and 100-140 parts by weight of coal tar to obtain a premix liquid; (2) The premix liquid is transported to the reaction chamber for combustion reaction, natural gas is used as fuel, the reaction temperature is controlled at 1700-1900°C, the reaction time is controlled at 5-9ms, tap water is used to atomize the flame to extinguish the combustion reaction, and a mixed flue gas is obtained; (3) passing the generated mixed flue gas into a heat exchange device for cooling, and the temperature after cooling is controlled below 280°C; (4) The mixed flue gas is cooled and enters the filter bag filtration system for flue gas separation. The filter bag collects carbon-silicon composite material particles, and the vibration system is started to remove the carbon-silicon composite material from the filter bag. The carbon-silicon composite material is crushed by the nano-crusher through the conveying system, and the blocky carbon-silicon composite material is made into powder; (5) The powdered carbon-silicon composite material enters a granulator through a pipeline, and is formed into granules under tap water atomization and a high-speed rotating granulation system. After drying, the carbon-silicon composite material is obtained.

2. The method for preparing the carbon-silicon composite material according to claim 1, characterized in that: In step (1), the particle size of the silica aerogel is 15-20 nm.

3. The method for preparing the carbon-silicon composite material according to claim 1, characterized in that: In step (1), the weight average molecular weight of the ethylene-butadiene rubber is 250,000-450,000.

4. The method for preparing the carbon-silicon composite material according to claim 1, characterized in that: In step (1), the specific mixing steps of the premix liquid are as follows: S1: First, the ethylene-butadiene rubber is melted, and the melting temperature is controlled at 65-70°C; after melting for 1-2 minutes, the ethylene-butadiene rubber is cut into pieces, and the pieces are left for 6-8 hours before being cooled to room temperature; S2: Put coal tar into a stirring tank, control the temperature at 160-170°C, put ethylene-butadiene rubber into the stirring tank, stir at a speed of 70-90 rpm, and stir for 15-20 min; S3: After the ethylene-butadiene rubber and coal tar are completely dissolved, add the silica aerogel and stir for 10-12 minutes. After mixing evenly, a premix liquid is obtained.

5. The method for preparing the carbon-silicon composite material according to claim 1, characterized in that: In step (2), the premix liquid and air are sprayed into the reaction chamber through a nozzle together, the flow rate of the premix liquid is 450-550 m / s, and the volume ratio of the premix liquid to air is 1:(15-25).

6. The method for preparing the carbon-silicon composite material according to claim 1, characterized in that: In step (4), the rotation speed of the nano-crusher is 2800-3000 rpm, and the crushing time is 5-8 s.

7. The method for preparing the carbon-silicon composite material according to claim 1, characterized in that: In step (5), during granulation, the mass ratio of the powdered carbon-silicon composite material to water is 1:(0.65-0.75).

8. A carbon-silicon composite material prepared by the method according to any one of claims 1 to 7.

9. A rubber sealing product, characterized in that: The rubber sealing product comprises the following components in parts by weight: 100 parts of ethylene-butadiene rubber; 45-55 parts of the carbon-silicon composite material as claimed in claim 8; 1-2 parts of coupling agent; 1-4 parts of antioxidant; 3-5 parts of zinc oxide; 1.5-2 parts of stearic acid; 1-2 parts of protective wax; 1.5-2.5 parts of accelerator; 0.2-0.4 parts of vulcanizing agent.

10. The rubber sealing product according to claim 9, characterized in that: At least one of (a) to (d): (a) the coupling agent is coupling agent SI-69; (b) the antioxidant includes at least one of antioxidant RD and antioxidant NBC; (c) The accelerator comprises at least one of thiazole, xanthocyanamide, thiuram and DTDM accelerators. (d) The vulcanizing agent includes sulfur and vulcanizing agent DCP.